2018
DOI: 10.1523/jneurosci.2031-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

BMP-Responsive Protease HtrA1 Is Differentially Expressed in Astrocytes and Regulates Astrocytic Development and Injury Response

Abstract: Astrocytes perform a wide array of physiological functions, including structural support, ion exchange, and neurotransmitter uptake. Despite this diversity, molecular markers that label subpopulations of astrocytes are limited, and mechanisms that generate distinct astrocyte subtypes remain unclear. Here we identified serine protease high temperature requirement A 1 (HtrA1), a bone morphogenetic protein 4 signaling regulated protein, as a novel marker of forebrain astrocytes, but not of neural stem cells, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…It solubilizes protein fibrils and disintegrates the fibrillary core structure, allowing productive interaction of aggregated polypeptides with the active site for rapid degradation. It has also been shown that brain injury induces HTRA1 expression in reactive astrocytes, and loss of HTRA1 leads to an impairment in wound closure accompanied by increased proliferation of endothelial and immune cells (Chen et al 2018). It is possible that obesity and insulin resistance related down-regulation of HTRA1 participates in the development of some obesity complications.…”
Section: Discussionmentioning
confidence: 99%
“…It solubilizes protein fibrils and disintegrates the fibrillary core structure, allowing productive interaction of aggregated polypeptides with the active site for rapid degradation. It has also been shown that brain injury induces HTRA1 expression in reactive astrocytes, and loss of HTRA1 leads to an impairment in wound closure accompanied by increased proliferation of endothelial and immune cells (Chen et al 2018). It is possible that obesity and insulin resistance related down-regulation of HTRA1 participates in the development of some obesity complications.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Now, the NVU is a tool that can be used to understand normal brain physiology as well as the pathophysiology of numerous neurological disorders. [24][25][26][27][28][29] Conversely, the malfunction of astroglia in the NVU (i.e., "astrogliopathy") [30][31][32][33][34] induces neuronal dysfunction, leading to various neurological disorders including cerebrovascular disease (e.g., stroke and small vessel disease-like Binswanger's disease and cerebral autosomaldominant arteriopathy with subcortical infarct and leukoencephalopathy [CADASIL]/ 35 cerebral autosomal recessive arteriopathy with subcortical infarct and leukoencephalopathy [CARASIL]), 36,37 neurodegenerative disease (e.g., Alzheimer's disease, 38,39 Parkinson's disease, 40,41 and amyotrophic lateral sclerosis [ALS]), [42][43][44] and neuroimmunological disease (e.g., multiple sclerosis [MS], [45][46][47][48] and neuromyelitis optica spectrum disorder [NMOSD]). 49,50 This review will focus on the supportive roles of astroglia in the NVU from the perspective of three major metabolic compartments with neurons: (i) glucose and lactate; (ii) fatty acid and ketone bodies (KBs); and (iii) D-and L-serine.…”
Section: Introductionmentioning
confidence: 99%
“…Down-expressed HtrA1 is related to a variety of neurological diseases. HtrA1 could mediate transforming growth factor-β hydrolysis and bone morphogenetic protein inhibition to prevent neural stem cell proliferation and differentiation inhibition [49]. In this study, the treatment of ICA reversed CUMSinduced Htra1 reduction in CSF, neurogenesis dysfunction and neuronal loss in DG, suggesting that the antihippocampal damage effect of ICA may be related to the regulation of Htra1 content in CSF.…”
Section: Discussionmentioning
confidence: 51%